Artificial intelligence and gender stereotypes: reflections, perpectives and digital innovation for inclusion at school - Filippone, Alfonso; Papa, Giulia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2024)
This article describes the experience conducted by 152 trainee teachers who, within the practical exercises of the Laboratory of Teaching of Education and the Anthropological Area, within the Specialization Course for Educational Support Activities for Students with Disabilities (Secondary School) at the University of Foggia, have planned and implemented a multimedia project with the aim of carrying out a reflection on the concept of gender stereotyping in light of the advent of new technologies and, in particular, artificial intelligence, proposing digital innovation project perspectives that can be pursued within the world of school to promote inclusion. Starting from an analysis of the needs related to the problems related to the presence of prejudices and gender stereotypes in today's society, and in particular in the youth world, the experience conducted has on the one hand offered food for thought on the impact that AI has on the different aspects of our lives and on the gender discrimination perpetuated by it, on the other hand it proposes an inclusive and sustainable design model, based on the use of AI and new digital and multimedia technologies, aimed at promoting inclusion by breaking down gender stereotypes through study and knowledge. The digital product obtained from this study, initially designed and created in a laboratory format by the teachers in training, was then submitted to their students, configuring itself as a tool that can contribute to the fight against gender inequalities, promote inclusion at school and be accessible, informative, flexible and engaging for all students.